First Molecular Characterization of Hypoderma actaeon in Cattle and Red Deer (Cervus elaphus) in Portugal - Ahmed, Haroon; Sousa, Sergio Ramalho; Simsek, Sami; Anastacio, Sofia; Kilinc, Seyma Gunyakti (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2017)
Hypoderma spp. larvae cause subcutaneous myiasis in several animal species. The objective of the present investigation was to identify and characterize morphologically and molecularly the larvae of Hypoderma spp. collected from cattle (Bos taurus taurus) and red deer (Cervus elaphus) in the district of Castelo Branco, Portugal. For this purpose, a total of 8 larvae were collected from cattle (n=2) and red deer (n=6). After morphological identification of Hypoderma spp. larvae, molecular characterization was based on PCR-RFLP and mitochondrial CO1 gene sequence analysis. All larvae were morphologically characterized as the third instar larvae (L3) of H. actaeon. Two restriction enzymes were used for molecular identification of the larvae. TaqI restriction enzyme was not able to cut H. actaeon. However, MboII restriction enzyme differentiated Hypoderma species showing 210 and 450 bp bands in H. actaeon. Furthermore, according to the alignment of the mt-CO1 gene sequences of Hypoderma species and to PCR-RFLP findings, all the identified Hypoderma larvae were confirmed as H. actaeon. This is the first report of identification of Hypoderma spp. (Diptera; Oestridae) from cattle and red deer in Portugal, based on morphological and molecular analyses.
Keywords: Hypoderma actaeon; cattle; red deer; phylogenetic analysis; PCR-RFLP; Portugal